Callie Qudsiyyah's business development strategy uses SWOT analysis and the business model canvas - Suci Nuryani (Institute of Computer Science (IOCS), 2023)
This research was conducted to formulate Callie Qudsiyyah's business development strategy using the Business Model Canvas (BMC) in facing business competition. This research method uses descriptive qualitative methods. The process of obtaining data is carried out by conducting direct interviews with the owner of Callie Qudsiyyah. The results of this study prove that Callie Qudsiyyah already has a framework of nine elements of the Business Model Canvas (BMC) which is a reference for running a business, but there are still shortcomings in optimizing BMC for which researchers adopt a SWOT analysis (Strengths, Weakness, Opportunities, and Threats) to improve Callie Qudsiyyah's business development strategy using BMC. Optimization of Callie Qudsiyyah's strategy in improving business strategy by making more creative product designs and innovations on a scheduled basis, developing the quality of human resources (HR), especially the production department, strengthening marketing digitalization, collaborating with influencers and focusing on more specific target consumers and strengthening Uniq Selling Point and improving consumer services in a good and correct way of communication.